2013
DOI: 10.1016/j.scr.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

EZ spheres: A stable and expandable culture system for the generation of pre-rosette multipotent stem cells from human ESCs and iPSCs

Abstract: We have developed a simple method to generate and expand multipotent, self-renewing pre-rosette neural stem cells from both human embryonic stem cells (hESCs) and human induced pluripotent stem cells (iPSCs) without utilizing embryoid body formation, manual selection techniques, or complex combinations of small molecules. Human ESC and iPSC colonies were lifted and placed in a neural stem cell medium containing high concentrations of EGF and FGF-2. Cell aggregates (termed EZ spheres) could be expanded for long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(135 citation statements)
references
References 34 publications
4
129
0
Order By: Relevance
“…They were grown on Matrigel in feeder-free conditions. To generate neural progenitors, cells were accutased and lifted, then grown for up to 35 passages as floating neurospheres in epidermal growth factor and fibroblast growth factor (100 mg/ml) (68). Neural progenitors were then plated onto poly-ornithine/laminin-coated coverslips and differentiated toward striatal cultures for 42 days as previously described (33).…”
Section: Methodsmentioning
confidence: 99%
“…They were grown on Matrigel in feeder-free conditions. To generate neural progenitors, cells were accutased and lifted, then grown for up to 35 passages as floating neurospheres in epidermal growth factor and fibroblast growth factor (100 mg/ml) (68). Neural progenitors were then plated onto poly-ornithine/laminin-coated coverslips and differentiated toward striatal cultures for 42 days as previously described (33).…”
Section: Methodsmentioning
confidence: 99%
“…There are other cells types that use this procedure for expansion. An example are EZ spheres, neural stem cells generated from pluripotent stem cells 41 . This technique has great potential for use with other types of tissue that require constant cell-to-cell contact during expansion.…”
Section: Future Applicationsmentioning
confidence: 99%
“…The provided chopping protocol allows for the production of large-scale banks from one fetal sample greater than passage 10, an unlikely feat using standard passaging methods. While this method for passaging hNPCs is unconventional, it is growing in popularity and was recently, published with other cell types such as neural stem cells derived from human embryonic and induced pluripotent stem cells, enabling large scale expansion for various applications including in vitro disease modeling [41][42][43][44][45][46] 1. The two most important factors to address before chopping is sphere diameter and media conditioning or color.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, although primary cell lines can provide fully differentiated cells that have a close approximation of the native function, the collection of all cell types is not possible because of the level of invasion required to collect them, and the limited proliferative activity of primary cells can make reproducing experiments difficult. 9 On the contrary, human-derived iPS and ES cell lines can overcome these disadvantages. After the expansion of these pluripotent cell lines, a sufficient number of the desired types of cells can be prepared by using appropriate differentiation protocols, that is, these technologies can provide an opportunity to maintain specific somatic cells on a large scale and in a renewable way.…”
Section: Ips Cells For In Vitro Modeling Of Native Physiological Condmentioning
confidence: 99%
“…It has been observed that 30% to 40% of all patients have mutations in NLRP3 in only a small number (≈10%) of somatic cells, 50,51 despite the fact that nearly half of all patients with CINCA syndrome carry heterozygous gain-of-function mutations of the gene. 9,52 Recently, Tanaka et al 44 generated both NLP3 mutant and nonmutant iPS cell lines from patients with CINCA syndrome with somatic mosaicism and described their differentiation into macrophages. In this case, they succeeded in recapitulating the disease-relevant phenotype using only mutant macrophages derived from iPS cells, demonstrating that NLRP3-mutant macrophages are responsible for the pathogenesis of mosaic CINCA syndrome.…”
Section: Somatic Mosaicism In Cinca Syndromementioning
confidence: 99%